A Proposed Framework Of Islamic Governance For Awqaf - Ihsan, Hidayatul; Ayedh, Abdullah (Universiti Sains Islam Malaysia, 2024)
Along with the revival of waqf (plural awqal) institution, the attention to the call for good governance and best practices of waqf has emerged. It is widely agreed that the best practice of good governance should be adopted as it is one of the critical success factors for revitalizing awqaf institutions. As far as waqf study is concerned, there is no existing study on waqf governance. This is probably because the conception of governance was used exclusively in the commercial sectors. In fact, governance in charitable and not-for profit organizations is much related to demonstrating accountability to stakeholders. This paper attempts to review some Islamic concepts and values which underpin the governance framework for awqaf institutions and thus demonstrate the Islamic accountability of mutawalli (awqaf manager).